Manajemen Konflik dalam Organisasi - Dini Vientianty; Fildza Rasiqah; Nadiyah Mawaddah (Pusat Riset dan Inovasi Nasional, 2024)
Conflict Management in an organization is meant by someone who is an actor between someone outside and each other in a conflict. Conflict management is an approach based on processes that lead to forms of communication from outsiders and how they influence interests and realize self-interpretation in forming individual attitudes within the organization. In an organization, individuals and groups of workers are interrelated with the work of other parties. When a conflict arises in an organization, the cause is always identified as poor communication. Likewise, when a bad decision is made, poor communication becomes less efficient communication. However, conflict is not always detrimental but can also be beneficial in the long term. Meanwhile, according to the interactionist view, conflict is something that must be stimulated, because conflict can encourage change in the organization. Conflict can change behavior and can make the parties in conflict aware of their mistakes. Awareness of these mistakes will be able to increase productivity in the organization.